WOMEN LEADERSHIP DEVELOPMENT IN SPORTS ORGANIZATION - wanla , Arnon; Samahito , Supitr (Academic Journal of Thailand National Sports University, 2019)
The research objective waso study the importance of the role and leadership of female leader and the factors resulting in the female leadership. The data helps to create the solution in development of female leadership in Thai Sport Organization. This research’s method wasualitative and descriptive research. The data had een collected and analyzed by Questionnaire and Delphi technique. During the operation, they are monitoring and inspecting the content validity of the questionnaire by using the IOC (Index of Item-objective congruence). The result shown that there were 5 specialists who have a complete reliability to the entire questionnaire which can be evaluated to 0.791. The result conveyedhat the importance of the role in female leader in Sport Organization was still in a good level. However, the networking is still the problem that female leader in Sport Organization needs to be improved. The result also reveals the good level of the leadership in female leader in Sport Organization. Yet, there are some topic which needs to be enhanced such as the self- esteem improvement and sport expertise. Moreover, the data shows that there are 5 factors resulting in the female leadership including management skill, visionary leader, strong personality, trustworthiness and high experience. The solutions of Women Leadership Development in Sports Organization can be described as 3 stages. First, the most important stage is the motivation which requires 2 factors to be accomplished: strong self-esteem and good organizational culture. The next state is high proficiency. An efficient leader, especially woman, needs to accomplish 4 ways of proficiency which are strong personality, reliability, emotional development skill and sport expertise and experiences. The third is the management improvement. It is proved that the strong leadership in female Sport organization is resulted from the management behavior in the organization which requires 3 skills comprising of visionary skill, administration skill and transformational leadership. The evaluation has been processing for the entire development in order to maintain the strength and eliminate the weakness of female leader.